New trends in Sino-Russian entrepreneurship - Wantao Lai; Ye Dongmei; Duanan Zheng (Управление)
Not only the long history of Sino-Russian economic communication but also Good timing, geographical convenience and good human relations help build up a solid foundation for modern cooperation between China and Russia as well as provide entrepreneurs with good opportunities to process global operation in Russian market or Chinese market.. This paper explores some new trends in entrepreneurship, which are both in China and Russia and pinpoint the underlying reasons behind those new trends. The article studies the legal framework for the development of Chinese-Russian trade and economic relations. The bilateral trade of Russia and China with the introduction of innovative technologies has been considered. The work of Chinese entrepreneurs in Russia has been analyzed. The assessment of the Russian market and its potential by the Chinese has been given. The conclusion of bilateral Sino-Russian agreements, the establishment of joint ventures, as well as the difficulties that Chinese businessmen have to deal with in Russia have been described. The work of Russian entrepreneurs in China has been examined. The opportunities for Russians to do business in China have been shown. The interest of the Chinese government and business circles in Russian investments, bilateral economic and cultural cooperation has been noted. Сhinese regard such good relationships between China and Russia as “honeymoon”. Under “honeymoon”, it is believed that Chinese and Russian entrepreneurs should seize the opportunity, expanding cross-border e-commerce communication, promoting technical exchange, and creating a win-win situation for both Chinese and Russians.